Efficacy and Safety of Autologous Bone Marrow-Derived Stem Cell Transplantation in Patients with Type 2 Diabetes Mellitus: A Randomized Placebo-Controlled Study. Issue 9 (September 2014) - Bhansali, Anil; Asokumar, Premkumar; Walia, Rama; Bhansali, Shobhit; Gupta, Vivek; Jain, Ashish; Sachdeva, Naresh; Sharma, Rati Ram; Marwaha, Neelam; Khandelwal, Niranjan
There is a growing interest in cell-based therapies in T2DM as β-cell failure is progressive and inexorable with the advancing duration of disease. This prospective, randomized, single-blinded placebo-controlled study evaluates the efficacy and safety of autologous bone marrow-derived stem cell transplantation (ABMSCT) in T2DM. Twenty-one patients with triple oral antidiabetic drug failure and requiring insulin ≥0.4 IU per kg per day with HbA1c <7.5% were randomly assigned to an intervention ( n = 11) and control group ( n = 10) and followed for 12 months. Patients in the intervention group received ABMSCT through a targeted approach, and after 12 weeks, a second dose of stem cells was administered through the antecubital vein after mobilization with G-CSF, while the control group underwent a sham procedure. The primary end point was a reduction in insulin requirement by ≥50% from baseline while maintaining HbA1c <7%. Nine out of the 11 (82%) patients in the intervention group achieved the primary end point, whereas none of the patients in the control group did over the study period ( p = 0.002). The insulin requirement decreased by 66.7% in the intervention group from 42.0 (31.0-64.0) IU per day to 14.0 (0.0-30.0) IU per day ( p = 0.011), while in controls it decreased by 32.1% from 40.5 (31.8-44.3) IU per day to 27.5 (23.5-33.3) IU per day ( p = 0.008) at 12 months. The reduction in insulin requirement was significantly more in the intervention group compared to controls at both 6 ( p = 0.001) and 12 months ( p = 0.004). There was a modest but nonsignificant increase in HbA1c (%) in cases from 6.9% (6.4-7.2%) to 7.1% (6.6-7.5%) as well as in controls from 6.9% (6.2-7.0%) to 7.0% (6.9-7.5%). Ten out of 11 (91%) patients could maintain HbA1c <7% in the intervention group, whereas 6 out of 10 did (60%) in the control group ( p = 0.167). The glucagon-stimulated C-peptide significantly increased in treated cases compared to controls ( p = 0.036). The decrease in insulin requirement positively correlated with stimulated C-peptide ( r = 0.8, p = 0.001). In conclusion, ABMSCT results in a significant decrease in the insulin dose requirement along with an improvement in the stimulated C-peptide levels in T2DM. However, a greater number of patients with a longer duration of follow-up are required to substantiate these observations.